Post‐Procedural Troponin Elevation and Clinical Outcomes Following Transcatheter Aortic Valve Implantation. Issue 2 (February 2016) - Koskinas, Konstantinos C.; Stortecky, Stefan; Franzone, Anna; O'Sullivan, Crochan J.; Praz, Fabien; Zuk, Katazyrna; Räber, Lorenz; Pilgrim, Thomas; Moschovitis, Aris; Fiedler, Georg M.; Jüni, Peter; Heg, Dik; et al.
Abstract : Background: Biomarkers of myocardial injury increase frequently during transcatheter aortic valve implantation (TAVI). The impact of postprocedural cardiac troponin (cTn) elevation on short‐term outcomes remains controversial, and the association with long‐term prognosis is unknown. Methods and Results: We evaluated 577 consecutive patients with severe aortic stenosis treated with TAVI between 2007 and 2012. Myocardial injury, defined according to the Valve Academic Research Consortium (VARC)‐2 as post‐TAVI cardiac troponin T (cTnT) >15× the upper limit of normal, occurred in 338 patients (58.1%). In multivariate analyses, myocardial injury was associated with higher risk of all‐cause mortality at 30 days (adjusted hazard ratio [HR], 8.77; 95% CI, 2.07–37.12; P =0.003) and remained a significant predictor at 2 years (adjusted HR, 1.98; 95% CI, 1.36–2.88; P <0.001). Higher cTnT cutoffs did not add incremental predictive value compared with the VARC‐2–defined cutoff. Whereas myocardial injury occurred more frequently in patients with versus without coronary artery disease (CAD), the relative impact of cTnT elevation on 2‐year mortality did not differ between patients without CAD (adjusted HR, 2.59; 95% CI, 1.27–5.26; P =0.009) and those with CAD (adjusted HR, 1.71; 95% CI, 1.10–2.65; P =0.018; P for interaction=0.24). Mortality rates at 2 years were lowest in patients without CAD and no myocardial injury (11.6%) and highest in patients with complex CAD (SYNTAX score >22) and myocardial injury (41.1%). Conclusions: VARC‐2–defined cTnT elevation emerged as a strong, independent predictor of 30‐day mortality and remained a modest, but significant, predictor throughout 2 years post‐TAVI. The prognostic value of cTnT elevation was modified by the presence and complexity of underlying CAD with highest mortality risk observed in patients combining SYNTAX score >22 and evidence of myocardial injury.